THE COMMON PROBLEMS OF THAI UNIVERSITY UNDERGRADUATE STUDENTS ON ENGLISH PRONUNCIATION ERRORS - Watcharee Paisart (PUPIL: International Journal of Teaching, Education and Learning, 2025)
Thai students learn English as an international language. One of the goals for English teachers is to help students to be able to communicate in English. However, many factors are involved such as grammatical structure and vocabulary. Pronunciation is also one of those factors. A limited number of researches on Thai university students’ pronunciation errors could be found with the use of teacher’s observation and interview. Therefore, this study aims to bring those aspects into account. There were 122 Thai university participants in this study. Observation checklist and semi-structured interview were employed. Numbers of frequency and percentage were used for observation data; while coding, frequency, and percentage were used for interview data. The majority of them mispronounced (97.54%). Three major errors were found: (1) ending sounds, (2) stress, (3) starting sounds. The top outstanding finding among the pronunciation errors of most students was that they did not realize that their pronunciations were wrong. One interesting finding was that their pronunciation errors had been much influenced from their high school English teachers whose pronunciations might also incorrect and led to their mistakes in pronunciation in the same way. Additionally, the students’ misperception about English pronunciation in some words make them pronounce wrongly because they understand that the pronunciation of the sounds show professionalism, especially the “R” and the “S” sounds. Then, the findings can be applied to plan for English pronunciation lesson that English teachers can focus on while teaching.